Post-fledging parental care in the pale-breasted thrush, Turdus leucomelas (Passeriformes: Turdidae) - Medeiros Haddad, Renan N. [UNESP]; Batisteli, Augusto Florisvaldo [UNESP]; Ibañez-álamo, Juan D.; Pizo, Marco A. [UNESP] (FapUNIFESP (SciELO), 2024)
Parental division of offspring care in the post-fledging stage of passerines is scarcely studied, especially for neotropical species. We describe the division of parental care in the post-fledging stage of the pale-breasted thrush, Turdus leucomelas Vieillot, 1818, focusing on the food provisioning rate, its effects on fledgling vocalization and foraging, as well as the way parents divide their brood for care. We made direct observations on 13 fledglings from eight families (mean ± standard deviation: 1.88 ± 0.83 fledglings per family) for 70.2 hours. We found no differences in food provisioning rate between adult males and females, nor was it affected by brood age or size. Food provisioning rate was not associated with the frequency of foraging and vocalization by fledglings; foraging was the only behavior that varied with brood age, increasing in frequency. Although there was no difference between parents in food provisioning, pale-breasted thrushes presented four different arrangements of fledgling care: male-only care (while females incubated a new clutch), brood division between the two parents, female-only care (in the absence of a new nesting attempt), and biparental care (both adults take care of the same fledgling). The mode of parental care (uniparental or biparental) did not affect the rate of food provisioning to fledglings. The diversity in modes of brood division between parents was greater than expected, which calls for further studies to uncover the underlying reasons for such variation.
Keywords: breeding behavior; brood division; fledglings; parental provisioning; urban bird